KONSEP PENDIDIKAN DALAM PERSPEKTIF PEMIKIRAN IBNU SINA - Darliana Sormin; Muksana Pasaribu; Mira Rahmayanti Sormin; Robiyatul Robiyatul (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Abstract: This study is motivated by the current national education system, which is an adoption of Western educational theories. While the theories of Islamic education are sometimes often abandoned or ignored even do not know at all distinguish which educational theories originate in the West and which also come from the Islamic world. Whereas between the theories of Western education and Islam there are fairly basic differences. Basically, many classical Islamic thinkers, who had formulated an education system, included Ibn Sina. To obtain data relevant to this problem I used a descriptive analysis method, namely by providing a clear picture of the ideas and thoughts developed by Ibn Sina about the concept of education as well as trying to analyze it and compare it with the concept of modern education today. The results of the study show that Ibn Sina's thoughts about the concept of education can be seen through goals, materials, methods, educators and punishment. The concept is still very actual and relevant to be developed and should be emulated and developed by educational practitioners in this modern era.